2007
DOI: 10.3200/gntp.167.4.349-364
|View full text |Cite
|
Sign up to set email alerts
|

Pretend Companions (Imaginary Playmates): The Emergence of a Field

Abstract: Over the last century, investigation of pretend companions has developed as an emerging field. Although pretend companions are a commonplace childhood phenomenon and perhaps an epitome of children's imagination, that topic received little attention before the end of the 19th century. Only since the last decade has attention to it truly begun to burgeon. Broad developments in the history of thought and research on pretend companions fall into 6 stages: (a) early history, (b) early theory, (c) earliest empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…It has been suggested that CICs are a childhood form of auditory hallucinations experienced as part of normal development (Pearson et al, 2001). However, the focus of research in this field has largely been on the examination of this phenomenon within the broader context of pretend play (Klausen & Passman, 2007). This article builds upon the existing research and looks at the links between CICs and pathological auditory hallucinations (PAHs) experienced by adults, a previously under-researched area.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that CICs are a childhood form of auditory hallucinations experienced as part of normal development (Pearson et al, 2001). However, the focus of research in this field has largely been on the examination of this phenomenon within the broader context of pretend play (Klausen & Passman, 2007). This article builds upon the existing research and looks at the links between CICs and pathological auditory hallucinations (PAHs) experienced by adults, a previously under-researched area.…”
Section: Introductionmentioning
confidence: 98%
“…(Taylor, Cartwright, and Carlson 1993;Taylor 1999;Gleason, Sebanc, and Hartup 2000). While the phenomenon of ICs had been largely ignored within developmental psychology until the late 1990s (Klausen and Passman 2007), the first psychiatric investigation into the nature of these companions were carried out in the 1940s (Bender and Vogel 1941;Svendsen, 1934;Ames and Learned 1946).…”
mentioning
confidence: 99%
“…The creation of these pretend games requires them to create a world with a set of rules that are often quite different from their everyday environments. These fantastic settings, or paracosms (Klausen & Passman, 2007), often play with the boundary between the "real" world and alternative systems. The functions of imaginary companions in child development are discussed next followed by a pilot study we conducted.…”
mentioning
confidence: 99%